A gradient structure wear-resistant coating and preparation method thereof

By preparing a gradient structure wear-resistant coating on the metal substrate surface of the hydraulic motor distribution pair, the wear problem of the distribution pair under low speed heavy load conditions is solved, and higher wear resistance and hardness are achieved.

CN119243147BActive Publication Date: 2025-04-25ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411787461.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-25
Estimated Expiration
2044-12-06

Smart Images

  • Figure CN119243147B_ABST
    Figure CN119243147B_ABST
Patent Text Reader

Abstract

The present invention discloses a gradient structure wear-resistant coating and a preparation method thereof. The gradient wear-resistant coating comprises: (1) a base layer; (2) a plurality of transition layers of NiSi+irregular WC ceramic particle composite coatings; (3) a wear-resistant layer of NiSi+spherical WC ceramic particle composite coating; the gradient coating is prepared on the surface of a metal substrate; irregular WC ceramic particles are added to the NiSi substrate coating as a transition layer to achieve a smooth transition between different materials and reduce interface stress; spherical WC ceramic particles are added to the NiSi substrate coating as a wear-resistant layer; the gradient structure coating can reasonably control internal stress while improving wear resistance. The present invention can effectively resist wear and other mechanical damage, thereby extending the service life of parts. The three-layer gradient structure coating improves wear resistance while reasonably controlling internal stress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface strengthening coatings, and in particular relates to a gradient structure wear-resistant coating and a preparation method thereof. Background Art

[0002] Hydraulic transmission is widely used in large equipment such as engineering machinery, agricultural machinery, aerospace, etc. due to its advantages such as high power density and high limit power. Among them, hydraulic motor is an important actuator to realize rotary motion. As a multi-acting, low-speed, high-torque hydraulic motor, the inner curve hydraulic motor has a distribution pair formed by the rotating cylinder and the fixed distribution plate, which is one of the three key friction pairs of the motor. The distribution plate and the cylinder body are in surface contact and rotating sliding motion. The oil film in the gap of the distribution pair is controlled by the pressure boundary of the high-pressure oil port, the low-pressure oil port and the cylinder plunger cavity oil port at the same time. It is a bridge connecting the internal flow channel of the inner curve hydraulic motor and the hydraulic circuit of the entire rotary drive system. Under low-speed and heavy-load conditions, it is difficult to establish a lubricating oil film for the distribution pair. The distribution pair is in a mixed lubrication state. The material of the distribution plate is ductile iron, which is prone to abrasive wear and fatigue wear. The significant accumulated wear makes the sealing and bearing performance of the distribution pair interface continue to deteriorate nonlinearly with the service time, which seriously affects the service life of the inner curve hydraulic motor.

[0003] Many scholars have limited effect on improving the wear resistance of the distribution pair from the perspective of structural optimization and increased the complexity of processing, and have not solved the problem of surface wear from the root. Laser cladding technology is a new method of modifying the surface of materials using the energy provided by a high-energy laser beam. The application of laser cladding technology in the production and manufacturing of ductile iron distribution plates not only solves the problems of low automation and uncontrollable strengthening performance of traditional surface strengthening treatment methods, but also can accurately control the thickness of the cladding layer by adjusting the process parameters. However, during the laser cladding process, the oxidation of graphite in ductile iron will lead to defects such as pores, and the difference in thermal expansion coefficient between the cladding layer and the substrate may cause cracking, thereby affecting the strength and stability of the cladding layer. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies of the prior art and propose a gradient structure wear-resistant coating and a preparation method thereof, so as to obtain a distribution pair surface strengthening coating with both surface quality and wear resistance. While ensuring good metallurgical bonding between the coating and the substrate and between the coating, the wear resistance is also improved.

[0005] The objective of the present invention is achieved through the following technical scheme: a gradient structure wear-resistant coating, the gradient wear-resistant coating comprising: (1) a base layer; (2) a plurality of transition layers - NiSi + irregular WC ceramic particle composite coatings; (3) a wear-resistant layer - NiSi + spherical WC ceramic particle composite coating, the gradient coating is prepared on the surface of a metal substrate; a corresponding base layer is adopted according to different metal substrates; the content of NiSi decreases from bottom to top in the plurality of transition layers and the wear-resistant layers, and the content of WC ceramic particles increases; irregular WC ceramic particles are added as a transition layer in the NiSi matrix coating to achieve a smooth transition between different materials and reduce interface stress; spherical WC ceramic particles are added as a wear-resistant layer in the NiSi matrix coating, and the gradient structure coating can reasonably control the internal stress while improving the wear resistance.

[0006] Furthermore, the metal substrate is cast iron, and the base layer is Inconel 625 coating, which isolates the diffusion of graphite phase in the cast iron and improves the bonding strength between the coating and the cast iron substrate.

[0007] Furthermore, the content of spherical WC ceramic particles in the wear-resistant layer does not exceed 60wt%.

[0008] Furthermore, the transition layer is a single layer, which is a composite coating of 60wt% NiSi+40wt% irregular WC ceramic particles; and the wear-resistant layer is a composite coating of 40wt% NiSi+60wt% spherical WC ceramic particles.

[0009] On the other hand, the present invention also provides a method for preparing a gradient structure wear-resistant coating, comprising the following steps:

[0010] S1: Prepare gradient wear-resistant coating powder, select the base layer according to the metal substrate, the transition layer uses NiSi alloy powder + irregular WC ceramic particles, the wear-resistant layer uses NiSi alloy powder + spherical WC ceramic particles, and the powders used for the transition layer and the wear-resistant layer are evenly mixed and dried;

[0011] S2: pre-treat the surface of the metal substrate, remove the oxide layer and clean it;

[0012] S3: Start the fiber laser, six-axis robot, synchronous powder feeder and argon gas cylinder; the coaxial powder feeding laser head moves according to the robot arm program, the argon gas cylinder provides gas for the coaxial powder feeding laser head and synchronous powder feeder, and argon provides protective gas for the cladding substrate;

[0013] S4: feeding the base layer powder into the synchronous powder feeder and laser cladding the base layer;

[0014] S5: Replace the powder in the powder feeder with transition layer powder, and laser clad the transition layer on the base layer;

[0015] S6: replacing the powder in the powder feeder with the wear-resistant layer powder, and laser cladding the wear-resistant layer on the transition layer;

[0016] S7: After the preparation of the gradient wear-resistant coating is completed, turn off the fiber laser, the six-axis robot, the argon gas cylinder and the synchronous powder feeder.

[0017] Further, in step S1, the particle size of the Inconel 625 alloy powder is 53-150 μm, and the chemical composition is: Cr: 21.67wt%, Nb: 3.37wt%, Si: 0.16wt%, Fe: 2.49wt%, C: 0.01wt%, Mo: 8.75wt%, Ti: 0.01wt%, Al: 0.06 wt%, and Ni balance.

[0018] Furthermore, in step S1, the particle size of the NiSi powder alloy powder is 53-150 μm, and the chemical composition is: C: 0.6-1.0 wt%, B: 1.75 wt%, Si: 3.11 wt%, Fe: 0.26 wt%, Cr: 0.15 wt%, and Ni as the remainder.

[0019] Furthermore, in step S1, the particle size of the irregular WC ceramic particles added to the transition layer is 53~150μm, and the chemical composition is: Cr ≤ 0.1wt%, Ni: 0.75wt%, Fe: 0.62wt%, C: 3.9wt%, V<0.1wt%, W balance; the particle size of the spherical WC ceramic particles added to the wear-resistant layer is 53~150μm, and the chemical composition is: Cr ≤ 0.1wt%, Ni: 0.48wt%, Fe: 0.35wt%, C: 3.96wt%, O<0.05wt%, W balance.

[0020] Further, in step S4, the laser cladding parameters are: laser power 2000W, scanning speed 20 mm / s, powder feeding rate 1.2 r / min, spot diameter 4 mm, and overlap rate 50%; in step S5, the laser cladding parameters are: laser power 2400W, scanning speed 16 mm / s, powder feeding rate 1.2 r / min, spot diameter 4mm, and overlap rate 50%; in step S6, the laser cladding parameters are: laser power 1700W~3100 W, scanning speed 16 mm / s, powder feeding rate 1.3 r / min, spot diameter 4mm, and overlap rate 50%.

[0021] Furthermore, in step S3, the flow rates of the powder feeding gas and the shielding gas are 15 L / min and 7.5 L / min, respectively.

[0022] The beneficial results of the present invention are:

[0023] 1. The basic phase of the three-layer gradient structure coating is γ-Ni solid solution, and the main components include WC phase, whose diffraction peak is significantly enhanced, indicating that the retention of WC is higher. The presence of the transition layer helps to buffer the heat change and reduce the thermal decomposition of WC particles, thereby improving the mechanical properties of the coating;

[0024] 2. The surface microhardness of the three-layer gradient structure coating can reach up to 485 HV 0.2 ;

[0025] 3. The three-layer gradient coating has good wear resistance. Under the reciprocating friction wear test conditions of 50N test load, 4mm stroke, 2Hz frequency and 40min duration, the wear volume is the smallest, which is 1.72×10 -3 mm -3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 Schematic diagram of the composition of the laser cladding coating prepared in Examples 1-4 of the present invention.

[0028] Figure 2 X-ray diffraction patterns of the laser cladding coatings prepared in Examples 1-4 of the present invention.

[0029] Figure 3 Microstructure diagram of the laser cladding coating prepared in Examples 1-4 of the present invention.

[0030] Figure 4 The microhardness of the laser cladding coatings prepared in Examples 1-4 of the present invention.

[0031] Figure 5 The wear volume of the laser cladding coating prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0033] The present invention provides a gradient structure wear-resistant coating, which comprises: (1) a base layer; (2) a plurality of transition layers-NiSi+irregular WC ceramic particle composite coatings; (3) a wear-resistant layer-NiSi+spherical WC ceramic particle composite coating, wherein the gradient coating is prepared on the surface of a metal substrate; a corresponding base layer is adopted according to different metal substrates; the content of NiSi decreases from bottom to top in the plurality of transition layers and the wear-resistant layers, and the content of WC ceramic particles increases; irregular WC ceramic particles are added as a transition layer in the NiSi substrate coating to achieve a smooth transition between different materials and reduce interface stress; spherical WC ceramic particles are added as a wear-resistant layer in the NiSi substrate coating, and the gradient structure coating can reasonably control internal stress while improving wear resistance.

[0034] Example 1: A method for preparing a gradient structure wear-resistant coating provided by the present invention is as follows:

[0035] S1: Prepare gradient wear-resistant coating powder, the base layer uses Inconel 625 alloy powder, the transition layer uses NiSi alloy powder + 40wt% WC irregular ceramic particles, the wear-resistant layer uses NiSi alloy powder + 60wt% WC spherical ceramic particles, and the powders of the transition layer and the wear-resistant layer are mixed by a ball mill, the speed is fixed at 400rpm, the duration is 0.8h, and the weight ratio of grinding balls to powder is 10:1. Dry the powder in a vacuum drying furnace at 45℃ for 8 hours to remove water vapor in the powder;

[0036] Among them, the particle size of Inconel 625 alloy powder is 53~150μm, and the chemical composition is: Cr: 21.67wt%, Nb: 3.37wt%, Si: 0.16wt%, Fe: 2.49wt%, C: 0.01wt%, Mo: 8.75wt%, Ti: 0.01wt%, Al: 0.06wt%, Ni balance; the particle size of NiSi powder alloy powder is 53~150μm, and the chemical composition is: C: 0.6~1.0wt%, B: 1.75wt%, Si: 3.11wt%, Fe: 0.26wt%, Cr: 0.15wt%, Ni balance; the particle size of irregular WC ceramic particles added to the transition layer is 53~150μm, and the chemical composition is: Cr≤0.1wt%, Ni: 0.75wt%, Fe: 0.62wt%, C: 3.9wt%, V<0.1wt%, W balance; the particle size of the spherical WC ceramic particles added to the wear-resistant layer is 53~150μm, and the chemical composition is: Cr≤0.1wt%, Ni: 0.48wt%, Fe: 0.35wt%, C: 3.96wt%, O<0.05wt%, W balance;

[0037] S2: A hydraulic motor valve plate made of QT600-3 material was selected as the cladding substrate. The QT600-3 substrate was processed into a size of 50×50×10 mm using an electric spark wire cutting machine. After the surface was polished with an angle grinder, the surface was cleaned with acetone and ethanol to remove oil stains.

[0038] S3: Start the fiber laser, six-axis robot, synchronous powder feeder and argon gas cylinder. The flow rates of powder feed gas and shielding gas are set to 15 L / min and 7.5 L / min respectively;

[0039] S4: Inconel 625 alloy powder was added into the synchronous powder feeder to perform laser cladding on the base layer. The parameters were: laser power 2000W, scanning speed 20 mm / s, powder feeding rate 1.2 r / min, spot diameter 4 mm, overlap rate 50%, and thickness 0.6 mm.

[0040] S5: Replace the powder in the synchronous powder feeder and laser clad the transition layer on the base layer. The parameters are: laser power 2400W, scanning speed 16 mm / s, powder feeding rate 1.2 r / min, spot diameter 4mm, overlap rate 50%, thickness 0.7mm;

[0041] S6: Replace the powder in the synchronous powder feeder and laser clad the wear-resistant layer on the transition layer. The parameters are: laser power 1700W~3100W, scanning speed 16 mm / s, powder feeding rate 1.3 r / min, spot diameter 4mm, overlap rate 50%, thickness 0.75mm;

[0042] S7: After the preparation of the gradient wear-resistant coating is completed, turn off the fiber laser, the six-axis robot, the argon gas cylinder and the synchronous powder feeder.

[0043] Example 2: The preparation process of a single-layer coating as a comparison is as follows:

[0044] The difference between this embodiment and embodiment 1 is that there are no steps S5 and S6, and only a base layer Inconel 625 alloy coating is clad on the QT600-3 substrate, which is a single-layer coating;

[0045] Example 3: The preparation process of the double-layer coating as a comparison is as follows:

[0046] The difference between this embodiment and embodiment 1 is that there is no step S6, and the first and second coating steps are the same as those in embodiment 1, and the second coating is a NiSi alloy + 40wt% WC irregular ceramic particle additive coating, which is a double-layer coating;

[0047] Example 4: The preparation process of the double-layer coating with different alloy contents as a comparison is as follows:

[0048] The difference between this embodiment and embodiment 1 is that there is no step S5, the first layer step is the same as that of embodiment 1, and the second layer coating step is consistent with step S5 in the embodiment, which is a NiSi alloy + 60wt% WC spherical ceramic particles added coating, which is a double-layer coating;

[0049] The gradient wear-resistant coating interface and its mechanical properties are characterized as follows:

[0050] The samples prepared in Examples 1-4 were respectively tested for their phase composition using an X-ray diffractometer (XRD), the cross-sectional morphology of the cladding layer was observed using a scanning electron microscope and the organizational characteristics were analyzed, the hardness of the coating was measured using a Vickers hardness tester, and the friction and wear properties were measured by a wear test using a reciprocating friction and wear tester under the test conditions of a test load of 50N, a stroke of 4mm, a frequency of 2Hz, and a duration of 40min. The wear scar morphology was observed using a scanning electron microscope and the wear mechanism was analyzed; the measurement results are shown in Figure 1-Figure 5 , the measurement results are shown.

[0051] exist Figure 1 In the middle: (a) is the sample of cladding the first layer of Inconel625 powder, cladding the second layer of NiSi powder + 40wt% WC irregular ceramic particle coating, cladding the third layer of NiSi powder + 60wt% WC spherical ceramic particle cladding layer, (b) is the sample of cladding one layer of Inconel625 powder cladding layer; (c) is the sample of cladding the first layer of Inconel625 powder, cladding the second layer of NiSi powder + 40wt% WC irregular ceramic particle coating cladding layer; (d) is the sample of cladding the first layer of Inconel625 powder, cladding the second layer of NiSi powder + 60wt% WC spherical ceramic particle cladding layer.

[0052] pass Figure 2 , Example 1-4, analyze the XRD patterns of different coatings, according to the phase analysis results show that: the basic phase of Inconel625 coating is γ-Ni solid solution, the multilayer coating is mainly composed of γ-Ni (basic phase), Ni 3 B. Ni 2 Si, WC, W 2 C.W. 3 C and M 6C composition; compared with the double-layer coating, the peak values ​​of the diffraction peaks corresponding to 2θ=31.47°, 35.63° and 48.27° of the three-layer gradient coating are significantly increased. The diffraction peaks correspond to the WC phase, indicating that the WC added phase of the outermost layer of the three-layer coating is more retained in the coating matrix, mainly due to the transition effect of the second layer. The existence of the transition layer can buffer the heat and make the temperature change more gentle, thereby reducing the thermal decomposition of WC particles. The WC in the transition layer can form a stable interface to prevent excessive concentration of thermal energy of the outer WC particles, reduce the risk of decomposition, and improve the mechanical properties of the cladding layer.

[0053] pass Figure 3 ,Examples 1-4, the surface quality of the four coatings is good, without obvious cracks and pores, and the WC ceramic additive phase is relatively intact in the coating.

[0054] pass Figure 4 , Example 1-4, the microhardness of the matrix is ​​215 HV 0.2 The surface hardness of the gradient three-layer coating in Example 1 is the highest, which is 485 HV 0.2 The hardness of the Inconel625 single-layer coating in Example 2 is the lowest, with a surface hardness of 243 HV. 0.2 The microhardness of the double-layer coatings in Examples 3 and 4 is 395 HV 0.2 and 418 HV 0.2 In summary, the microhardness of the three-layer gradient structure coating is the highest, which is 2.26 times the microhardness of the substrate, 99.6% higher than the microhardness of the Inconel625 single-layer coating, and 22.78% and 16% higher than the microhardness of the double-layer coating in Examples 3 and 4. The improvement in hardness of the three-layer gradient coating compared to the double-layer coating is due to its unique gradient structure. The transition layer effectively alleviates the thermal stress difference between the layers of the coating, reduces the risk of thermal cracks and particle decomposition, and ensures the stability of WC particles at high temperatures. At the same time, the transition layer enhances the bonding force between the layers, prevents interlayer peeling or fracture, and thus improves the overall mechanical properties of the coating. Such structural optimization makes the three-layer gradient coating superior to the double-layer and single-layer coatings in wear resistance.

[0055] pass Figure 5 , Examples 1, 2, 3, and 4. The wear volume of the gradient three-layer coating in Example 1 is the smallest, which is 1.72×10 -3 mm -3 The wear volume of the Inconel 625 single-layer coating in Example 2 is the largest, which is 26.99×10 -3 mm -3 The wear volume of the double-layer coating in Example 3 is 5.45×10 -3 mm -3The wear volume of the double-layer coating in Example 4 is 3.15×10 - 3 mm -3 , so the wear resistance of the three-layer coating in Example 1 is 1.73 and 3.16 of the double-layer coating in Examples 3 and 4. In summary, the three-layer gradient coating in Example 1 exhibits the best wear resistance, which is much lower than other coatings. This is mainly attributed to the advantages of the gradient structure. The gradient coating effectively alleviates thermal stress through the transition design between layers, reducing the risk of cracking and falling off. At the same time, the doped WC particles are more evenly distributed in the coating, enhancing the hardness and wear resistance of the coating. In contrast, the double-layer coating lacks a transition layer and is easily affected by thermal stress, resulting in poor wear resistance. Although the single-layer coating can provide certain protection, due to the lack of gradient design, it cannot effectively alleviate the thermal stress difference, and is prone to cracking and falling off, thereby reducing its wear resistance. Therefore, the three-layer gradient coating has better comprehensive wear resistance.

[0056] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A gradient structure wear-resistant coating, characterized in that: The gradient wear-resistant coating comprises: (1) a base layer; (2) a plurality of transition layers - NiSi + irregular WC ceramic particle composite coatings; (3) a wear-resistant layer - NiSi + spherical WC ceramic particle composite coating, and the gradient wear-resistant coating is prepared on the surface of a metal substrate; the metal substrate is cast iron, and the base layer is an Inconel 625 coating to isolate the diffusion of the graphite phase in the cast iron and improve the bonding force between the coating and the cast iron substrate; the transition layer is a 60wt% NiSi + 40wt% irregular WC ceramic particle composite coating; the wear-resistant layer is a 40wt% NiSi + 60wt% spherical WC ceramic particle composite coating, the particle size of the NiSi powder alloy powder is 53~150μm, and the chemical composition is: C: 0.6~1.0wt%, B: 1.75wt%, Si: 3.11wt%, Fe: 0.26wt%, Cr: 0.15wt%, and Ni balance.

2. A method for preparing a gradient structure wear-resistant coating according to claim 1, characterized in that: The following steps are involved: S1: Prepare gradient wear-resistant coating powder, select the base layer according to the metal matrix, the transition layer uses NiSi alloy powder + irregular WC ceramic particles, the wear-resistant layer uses NiSi alloy powder + spherical WC ceramic particles, and the powders used for the transition layer and the wear-resistant layer are uniformly mixed and dried; the particle size of the NiSi powder alloy powder is 53~150μm, and the chemical composition is: C: 0.6~1.0wt%, B: 1.75wt%, Si: 3.11wt%, Fe: 0.26wt%, Cr: 0.15wt%, Ni balance; S2: pre-treat the surface of the metal substrate, remove the oxide layer and clean it; S3: Start the fiber laser, six-axis robot, synchronous powder feeder and argon gas cylinder; the coaxial powder feeding laser head moves according to the robot arm program, the argon gas cylinder provides gas for the coaxial powder feeding laser head and synchronous powder feeder, and argon provides protective gas for the cladding substrate; S4: feeding the base layer powder into the synchronous powder feeder and laser cladding the base layer; S5: Replace the powder in the powder feeder with transition layer powder, and laser clad the transition layer on the base layer; S6: replacing the powder in the powder feeder with the wear-resistant layer powder, and laser cladding the wear-resistant layer on the transition layer; S7: After the preparation of the gradient wear-resistant coating is completed, turn off the fiber laser, the six-axis robot, the argon gas cylinder and the synchronous powder feeder.

3. The method for preparing a gradient structure wear-resistant coating according to claim 2, characterized in that: In step S1, the particle size of the alloy powder of the Inconel 625 coating is 53-150 μm, and the chemical composition is: Cr: 21.67wt%, Nb: 3.37wt%, Si: 0.16wt%, Fe: 2.49wt%, C: 0.01wt%, Mo: 8.75wt%, Ti: 0.01wt%, Al: 0.06wt%, Ni balance.

4. The method for preparing a gradient structure wear-resistant coating according to claim 3, characterized in that: In step S1, the irregular WC ceramic particles added to the transition layer have a particle size of 53~150μm, and the chemical composition is: Cr ≤ 0.1wt%, Ni: 0.75wt%, Fe: 0.62wt%, C: 3.9wt%, V < 0.1wt%, W balance; the spherical WC ceramic particles added to the wear-resistant layer have a particle size of 53~150μm, and the chemical composition is: Cr ≤ 0.1wt%, Ni: 0.48wt%, Fe: 0.35wt%, C: 3.96wt%, O < 0.05wt%, W balance.

5. The method for preparing a gradient structure wear-resistant coating according to claim 2, characterized in that: In step S4, the laser cladding parameters are: laser power 2000W, scanning speed 20 mm / s, powder feeding rate 1.2 r / min, spot diameter 4 mm, and overlap rate 50%; in step S5, the laser cladding parameters are: laser power 2400W, scanning speed 16 mm / s, powder feeding rate 1.2 r / min, spot diameter 4mm, and overlap rate 50%; in step S6, the laser cladding parameters are: laser power 1700W~3100 W, scanning speed 16 mm / s, powder feeding rate 1.3 r / min, spot diameter 4mm, and overlap rate 50%.

6. The method for preparing a gradient structure wear-resistant coating according to claim 2, characterized in that: In step S3, the flow rates of the powder feeding gas and the shielding gas are 15 L / min and 7.5 L / min, respectively.

Citation Information

Patent Citations

  • High-stability high-speed train brake disc coating and preparation method thereof

    CN113913810A

  • Ultrahigh-speed laser cladding composite coating brake disc as well as preparation method and application thereof

    CN114959692A